Environmental health risk assessment in opthalmic lens manufacturing - De Vera, Estrella M. (2008)
Records in an ophthalmic lens manufacturing facility located in Laguna show an average of three accidents annually for the past five years. Also, occupational illness such as cases of eye and skin irritation is also significantly high with 9.14 severity rate for the year 2007. Furthermore, clinic report indicates 17 cases of mild hearing loss for 2007 and one case of carpal tunnel syndrome (CTS) in quarter one of 2008. Thus, this study is significant to review and evaluate the hazards and environmental health risks associated in an ophthalmic lens manufacturing.
The methodology of the study consisted of three main phases namely 1). hazard identification, 2). risk assessment and 3). risk characterization and analysis. The conventional type of assessment was not used. Instead, a method applicable to ophthalmic lens manufacturing was established. This is to have a simple approach of risk assessment that can be used by non-technical personnel which takes into consideration the existing controls established.
The first phase of the methodology involves process mapping to review tasks, equipment, hazardous substances, utilities and work practices involved in each process. For each process, the environmental health hazard was identified based on five categories namely chemical, physical, ergonomics, electrical and mechanical hazards. The consequence relating to each hazard and the situation category, were also identified.
In the risk assessment phase, a system to evaluate the risk was developed. The risk assessment was function of probability and severity factors. The controls in place for each hazard were incorporated in the assessment. Thus, the hazard with effective control in place has lower risks compared with hazard that has no control at all. After the evaluation of each hazard, the total risk for each process was evaluated by summing up all individual risks estimated for each hazard in a double iteration.
The last phase of the methodology is risk characterization. This phase categorized the risk into High, Medium and Low Risk. Risk scoring 130 and above were characterized as high risk. Risk scoring between 75 and 130 were characterized as medium risk with score 75 and below was considered to be low risk.
Results showed that the top two highest risks were high index monomer preparation and low index degasketting / disassembly process with score of 322 and 199, respectively. For the high index monomer preparation, physical, chemical and mechanical hazards were contributing to the overall risk due to poor control on man, material, machine and method factors were. For low index degasketting / disassembly process, mechanical, chemical, physical and ergonomics were the contributing hazards. The main cause for high risk in this process is the poor control on physical hazard specifically noise and ergonomics.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Health risk assessment -- Philippines; Industrial facilities -- Philippines